Customer retention: investigating the dimensions in telecommunication industry - Gui, Jin Kiant (Universiti Malaysia Sarawak (UNIMAS), 2013)
This paper aims to investigate the relationship between factors affecting customer retention in the telecommunication industry. Customer satisfaction, customer trust and service quality are three identified factors affecting customer retention in the industrj Convenience sampling technique used to collect the the sample with 170 questionnaires was distributed to the target respondents. Pearson Coefficient Correlation and regression analysis utilized in order to determine the relationship of the variables and the data analyzed using a computer software package -Statistical Package for Social Science (18.0). The finding confirmed that the three factors have positive and significant relationship with customer retention. From the finding also postulated that most significant variable that influences the variance in customer retention is service quality.